2022
DOI: 10.1159/000521631
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer: Current Multimodality Treatment Options and the Future Impact of Molecular Biological Profiling

Abstract: <b><i>Background:</i></b> Pancreatic cancer (PDAC) – even if deemed resectable – has still a dismal prognosis and is the seventh leading cause of global cancer-related death with rising incidence worldwide. <b><i>Summary:</i></b> Surgical resection at best in combination with adjuvant systemic chemotherapy is the only potentially curative treatment. Surgical treatment has substantially improved over the last years with significantly reduced perioperative morbidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…The stemness and aggressiveness of refractory PTC have not yet been revealed. Outcomes from the advancement of anti-cancer drugs finding many studies have described that pre-operative chemotherapy can extend the survival rates after surgery [ 44 , 45 , 46 , 47 ]. Nonetheless, no selective therapeutic options have been accepted as the basal adjuvant or neoadjuvant background for drug-resistant cancer [ 48 , 49 , 50 ], and a substantial number of anti-cancer drug-resistant cancer patients have died; therefore, unmet medical needs have consistently increased.…”
Section: Discussionmentioning
confidence: 99%
“…The stemness and aggressiveness of refractory PTC have not yet been revealed. Outcomes from the advancement of anti-cancer drugs finding many studies have described that pre-operative chemotherapy can extend the survival rates after surgery [ 44 , 45 , 46 , 47 ]. Nonetheless, no selective therapeutic options have been accepted as the basal adjuvant or neoadjuvant background for drug-resistant cancer [ 48 , 49 , 50 ], and a substantial number of anti-cancer drug-resistant cancer patients have died; therefore, unmet medical needs have consistently increased.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the development of anti-cancer drugs, numerous studies have reported that preoperative chemotherapy improves the survival rates after surgery and demonstrated the effect of properly administered chemotherapy and performed surgery even when effective treatment was considered impossible [ 25 , 26 , 27 , 28 ]. Nevertheless, no treatment options have been accepted as the standard neoadjuvant or adjuvant setting for HCC [ 29 , 30 , 31 ], and considerable numbers of HCC patients with cancer died; therefore, unmet medical needs have steadily increased.…”
Section: Discussionmentioning
confidence: 99%
“…By ECBS, chemical pairs are considered as “similar” when their binding targets are identical or evolutionarily related. Among variants of ECBS models, the target-specific ensemble ECBS (TS-ensECBS) model was adapted for the virtual screening owing to the highest test accuracy in our previous study [ 26 ]. The TS-ensECBS model was built for SERCA (i.e., the ERCPs are only defined for SERCA and its homologous proteins).…”
Section: Methodsmentioning
confidence: 99%
“…Anticancer drug discovery has evolved and new therapeutic strategies against cancer have emerged. Thus, preoperative chemotherapy expands survival rates after surgery, and adequate chemotherapy and surgery are effective even in unfavorable clinical situations [ 43 , 44 , 45 , 46 ]. However, there are no effective therapeutic options for the management of antineoplastic-resistant cancer [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%